Large old trees increase growth under shifting climatic constraints: Aligning tree longevity and individual growth dynamics in primary mountain spruce forests. Issue 1 (12th October 2022) - Begović, Krešimir; Schurman, Jonathan S.; Svitok, Marek; Pavlin, Jakob; Langbehn, Thomas; Svobodová, Kristyna; Mikoláš, Martin; Janda, Pavel; Synek, Michal; Marchand, William; Vitková, Lucie; Kozák, Daniel; et al.
Abstract: In a world of accelerating changes in environmental conditions driving tree growth, tradeoffs between tree growth rate and longevity could curtail the abundance of large old trees (LOTs), with potentially dire consequences for biodiversity and carbon storage. However, the influence of tree‐level tradeoffs on forest structure at landscape scales will also depend on disturbances, which shape tree size and age distribution, and on whether LOTs can benefit from improved growing conditions due to climate warming. We analyzed temporal and spatial variation in radial growth patterns from ~5000 Norway spruce ( Picea abies [L.] H. Karst) live and dead trees from the Western Carpathian primary spruce forest stands. We applied mixed‐linear modeling to quantify the importance of LOT growth histories and stand dynamics (i.e., competition and disturbance factors) on lifespan. Finally, we assessed regional synchronization in radial growth variability over the 20th century, and modeled the effects of stand dynamics and climate on LOTs recent growth trends. Tree age varied considerably among forest stands, implying an important role of disturbance as an age constraint. Slow juvenile growth and longer period of suppressed growth prolonged tree lifespan, while increasing disturbance severity and shorter time since last disturbance decreased it. The highest age was not achieved only by trees with continuous slow growth, but those with slow juvenile growth followed by subsequent growth releases. Growth trend analysis demonstrated an increase in absolute growth rates in response to climate warming, with late summer temperatures driving the recent growth trend. Contrary to our expectation that LOTs would eventually exhibit declining growth rates, the oldest LOTs (>400 years) continuously increase growth throughout their lives, indicating a high phenotypic plasticity of LOTs for increasing biomass, and a strong carbon sink role of primary spruce forests under rising temperatures, intensifying droughts, and increasing bark beetle outbreaks. Abstract : Understanding growth dynamics and development of large old trees in montane primary forests amidst intensifying environmental pressures can help predict future forest development and ecosystem functioning. Slow growth early in a trees' life is essential for long lifespan, however, disturbance dynamics carry a defining role for achieving old age in primary forests. In response to the late 20th century rising temperatures, Western Carpathian primary spruce forests have shown a synchronous increase in productivity, indicating a high adaptive capacity to improving growing conditions, which could carry broad landscape consequences for the carbon sink potential of primary montane forests under changing climate.